Analyzing and Viewing the Development of Construction of the Philosophical View of Positivism - Ratna Wati (Riviera Publishing, 2024)
Philosophy is a discipline that aims to seek truth by exploring answers to fundamental questions. In its endeavors, philosophy interacts with the evolving results of science, including schools such as Neo-Positivism. This research aims to analyze and understand the differences in research paradigms, especially in social science, with a focus on positivism, constructivism, and critical paradigms. In addition, this research also describes the positivism paradigm and its three basic assumptions: ontology, epistemology, and methodology. The method used is a literature study with a descriptive-qualitative approach. The results show that the Neo-Positivism paradigm has a significant influence in the development of science and human civilization. Positivism emphasizes that science is the only valid form of knowledge and only observable facts can be used as objects of study. Thus, positivism rejects the existence of forces beyond facts that can be tested empirically. The implication of this research lies in a deeper understanding of how research paradigms contribute to the formation of scientific theories as well as the application of science in people's lives.